2020
DOI: 10.3390/ijms21124347
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5 Genotype as a Potential Pharmacodynamic Biomarker for Tacrolimus Therapy in Ulcerative Colitis in Japanese Patients

Abstract: Tacrolimus has been used to induce remission in patients with steroid-refractory ulcerative colitis. It poses a problem of large individual differences in dosage necessary to attain target blood concentration and, often, this leads to drug inefficacy. We examined the difference in mRNA expression levels of ATP binding cassette transporter B1 (ABCB1) between inflamed and non-inflamed tissues, and the influence of CYP3A5 genotype on tacrolimus therapy. The mRNA expression of CYP3A4 in colonic mucosa and that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…38 The extent of CYP3A5 activity in the colon is unclear, but recent data are in line with a significant role of CYP3A5 in tacrolimus intestinal firstpass elimination also in the colon. 39 Consistently, in our trial, tacrolimus exposure with PR-Tac was also lower in CYP3A5 expressors than in non-expressors (Table S12). This is more likely explained by higher intestinal first-pass elimination because comparable terminal half-life in both groups (Table S12) indicates that systemic elimination does not seem affected by CYP3A5 genotype.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…38 The extent of CYP3A5 activity in the colon is unclear, but recent data are in line with a significant role of CYP3A5 in tacrolimus intestinal firstpass elimination also in the colon. 39 Consistently, in our trial, tacrolimus exposure with PR-Tac was also lower in CYP3A5 expressors than in non-expressors (Table S12). This is more likely explained by higher intestinal first-pass elimination because comparable terminal half-life in both groups (Table S12) indicates that systemic elimination does not seem affected by CYP3A5 genotype.…”
Section: Discussionsupporting
confidence: 83%
“…A possible explanation could be that in expressors, CYP3A4 and CYP3A5 both contribute to tacrolimus metabolism and induction of CYP3A4 by SJW, if present, results in the same absolute increase in CYP3A activity in both expressors and non‐expressors but the relative increase in CYP3A activity is smaller in CYP3A5 expressors when CYP3A5 is not induced by SJW, as suggested by in vitro data 38 . The extent of CYP3A5 activity in the colon is unclear, but recent data are in line with a significant role of CYP3A5 in tacrolimus intestinal first‐pass elimination also in the colon 39 . Consistently, in our trial, tacrolimus exposure with PR‐Tac was also lower in CYP3A5 expressors than in non‐expressors (Table S12).…”
Section: Discussionmentioning
confidence: 73%
“…These autoimmune diseases responsible genes might be critical for the development of CD. Recently, study found that CXCL5 [454], S100A12 [455], OSM (oncostatin M) [456], LRG1 [457], LCN2 [458], CXCL1 [459], S100A9 [460], IFITM1 [461], XBP1 [462], MMP3 [457], IFITM3 [463], IL1B [464], GBP5 [465], HGF (hepatocyte growth factor) [466], CXCL9 [467], SLC11A1 [468], IL1RN [469], STAT1 [470], CYP27B1 [471], MMP1 [472], SOCS3 [473], TLR8 [474], CD55 [475], CCL28 [476], FCGR2A [477], CCL2 [478], CFB (complement factor B) [479], CD14 [480], GPR84 [481], PCSK9 [482], FOXP3 [483], LPL (lipoprotein lipase) [484], IL1R2 [485], TLR2 [486], MEFV (MEFV innate immuity regulator, pyrin) [487], VWF (von Willebrand factor) [488], NOD2 [489], DMBT1 [490], HSPA6 [491], TIMP1 [492], ICAM1 [493], EGR1 [494], CCL11 [495], IFNG (interferon gamma) [496], APOE (apolipoprotein E) [497] FGR (FGR proto-oncogene, Src family tyrosine kinase) [498], IL6 [499], SPP1 [192], IL11 [500], RNF186 [501], MMP2 [502], CD24 [503], SPHK1 [504], GZMB (granzyme B) [505], MUC5AC [506], SERPINA3 [507], TWIST1 [508], PLAU (plasminogen activator, urokinase) [509], CA2 [510], CA9 [510], CTLA4 [511], PADI4 [512], MMP13 [513], MPO (myeloperoxidase) [244], LEFTY1 [514], CA1 [515], MMP7 [513], ABCG2 [516], CYP2J2 [517], AICDA (activation induced cytidine deaminase) [518], CYP2D6 [519], CYP3A5 [52...…”
Section: Discussionmentioning
confidence: 99%
“…67 Yamamoto et al found that the tacrolimus dose to maintain equivalent blood concentrations was lower in patients carrying the cytochrome (CYP) 3A5*3/*3 than in those carrying the CYP3A5*1 genotype, and the concentration/dose ratio was significantly higher in the latter. 68 Ciclosporin is an option for treating acute severe UC, but it has a significant toxicity profile, with nephrotoxicity occurring in 6.3%. 7,69 Rat models have revealed that acute renal damage secondary to ciclosporin is due to vasoconstriction of the afferent arterioles, leading to diminished renal blood flow and glomerular filtration, with a consequent rise in serum creatinine.…”
Section: Tacrolimus and Ciclosporinmentioning
confidence: 99%